Comparison of a preferred versus non-preferred waterpipe tobacco flavour: subjective experience, smoking behaviour and toxicant exposure. Issue 3 (5th April 2017) - Leavens, Eleanor L; Driskill, Leslie M; Molina, Neil; Eissenberg, Thomas; Shihadeh, Alan; Brett, Emma I; Floyd, Evan; Wagener, Theodore L
Abstract : Introduction: One possible reason for the rapid proliferation of waterpipe (WP) smoking is the pervasive use of flavoured WP tobacco. To begin to understand the impact of WP tobacco flavours, the current study examined the impact of a preferred WP tobacco flavour compared with a non-preferred tobacco flavoured control on user's smoking behaviour, toxicant exposure and subjective smoking experience. Method: Thirty-six current WP smokers completed two, 45-minute ad libitum smoking sessions (preferred flavour vs non-preferred tobacco flavour control) in a randomised cross-over design. Participants completed survey questionnaires assessing subjective smoking experience, exhaled carbon monoxide (eCO) testing, and provided blood samples for monitoring plasma nicotine. WP smoking topography was measured continuously throughout the smoking session. Results: While participants reported an enhanced subjective smoking experience including greater interest in continued use, greater pleasure derived from smoking, increased liking and enjoyment, and willingness to continue use after smoking their preferred WP tobacco flavour (p values <0.05), no significant differences were observed in nicotine and carbon monoxide boost between flavour preparations. Greater average puff volume (p=0.018) was observed during the non-preferred flavour session. While not significant, measures of flow rate, interpuff interval (IPI), and total number of puffs were trending towards significance (p values <0.10), with decreased IPI and greater total number of puffs during the preferred flavour session. Discussion: The current study is the first to examine flavours in WP smoking by measuring preferred versus control preparations to understand the impact on subjective experience, smoking behaviour and toxicant exposure. The pattern of results suggests that even this relatively minor manipulation resulted in significant changes in subjective experience. These results indicate a possible need for regulations restricting flavours in WP tobacco as with combustible cigarettes.